Functionalization of developed bacterial cellulose with magnetite nanoparticles for nanobiotechnology and nanomedicine applications. (1st November 2020) - Chaabane, Laroussi; Chahdoura, Hassiba; Mehdaoui, Rahma; Snoussi, Mejdi; Beyou, Emmanuel; Lahcini, Mohammed; V Baouab, Mohamed Hassen
Graphical abstract: Highlights: Magnetic material from bacterial cellulose with Fe3 O4 NPs were synthesis. Fe3 O4 NP-INS-(DABC-EDA-Bzl) shows stronger antimicrobial and cytotoxic activities. Fe3 O4 NP-INS-(DABC-EDA-Bzl) has non-cytotoxicitiy towards normal cells. Fe3 O4 NP-INS-(DABC-EDA-Bzl) shows extraordinary platform in cancer chemotherapy. Abstract: This paper deals with the preparation of novel magnetic materials made from tetraaza macrocyclic Schiff base bacterial cellulose ligands with magnetite nanoparticles (Fe3 O4 NPs) through a multi-step procedure for antimicrobial and cytotoxic activities and chemotherapy in cancer treatment. First, the 2, 3-dialdehyde bacterial cellulose (DABC) was chemically modified by ethylenediamine (EDA) and benzil (Bzl) in the presence of ferrous ions. Then, the magnetite nanoparticles (Fe3 O4 NPs) was produced inside the complex [Fe(DABC-EDA-Bzl)Cl2 ] through a co-precipitation method. In nanobiotechnology, the magnetic [Fe3 O4 NP-INS-(DABC-EDA-Bzl)] material was showed moderate antimicrobial and cytotoxic activities against different species and cells, respectively. In particular, the magnetic [Fe3 O4 NP-INS-(DABC-EDA-Bzl)] material have not any cytotoxic activity towards peripheral blood mononucleocyte (PBMC) cells. Anti-tumor studies demonstrated that the magnetic [Fe3 O4 NP-INS-(DABC-EDA-Bzl)] material effectively inhibits the growth of the CT26 tumor model in BALB/c mice compared with other resulting materials throughout the experimental period and can be effective drug delivery in nanomedicine.